Financial Accounting System Untuk Mencapai Good Governance Pemerintah Kota Makassar (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This study discusses the financial accounting system to achieve good governance of the Makassar City Government. The formulation of the problem in this research is how to apply accrual-based accounting standards in the local government of Makassar City and how to implement the public sector financial accounting system in achieving good governance in the Makassar City government. This study aims to determine the extent to which the application of accounting standards and the implementation of the public sector financial accounting system in achieving good governance in the local government of Makassar City. The benefits of research are the benefits of theory and practice. This type of research is qualitative research. Sources of data used in this study are primary data and secondary data. Methods of data collection using interviews, documentation and library research. The results showed that the financial accounting system in the Makassar city government, especially at the Makassar City Regional Development Planning Agency (BAPPEDA) was in accordance with the rules set by the government and also the financial reporting was in accordance with the principles of good governance (transparency and accountability).